Achieving sustainable cultivation of ornamental plants - Reid, Michael (Burleigh Dodds Science Publishing, 2020)
Cover -- Half-Title -- Series -- Title -- Copyright -- Contents -- Series list -- Reviewers to acknowledge -- Introduction -- Part 1 Physiology and breeding -- 1 Environmental physiology of ornamental crops -- 1 Introduction -- 2 Propagation: sexual propagation -- 3 Propagation: asexual propagation -- 4 Vegetative development -- 5 Increasing plant mass -- 6 Reproductive development -- 7 Dormancy -- 8 References -- 2 Exploiting the genetic diversity of ornamentals -- 1 Introduction -- 2 Management of ornamental germplasm to exploit genetic diversity: collection strategy -- 3 In situ conservation methods -- 4 Ex situ conservation -- 5 Management of plant genetic resources in the Republic of Korea and in Japan -- 6 Management of plant genetic resources in the United States -- 7 Management of plant genetic resources in Canada -- 8 Management of plant genetic resources in Europe -- 9 Utilizing ornamental germplasm to exploit genetic diversity in cacti -- 10 Utilizing cacti to cope with the global climate change -- 11 Conclusions -- 12 References -- 3 Advances in conventional breeding techniques for ornamentals -- 1 Introduction -- 2 Current common breeding techniques in ornamentals -- 3 Conventional cross breeding and selection -- 4 Conclusion and future trends -- 5 References -- 4 Advances in tissue culture techniques for ornamental plant propagation -- 1 Introduction -- 2 Factors affecting tissue culture techniques -- 3 Tissue culture techniques -- 4 Future trends -- 5 References -- 5 Advances in molecular breeding of ornamentals -- 1 Introduction -- 2 Flowers as study organisms for early genetic research -- 3 Flower breeding in the nineteenth and twentieth centuries -- 4 Early use of biotechnology in marker-assisted breeding -- 5 Flower color -- 6 Flowering genes -- 7 Genetically engineered flowers (GMOs and GEOs) -- 8 Genome sequencing
Keywords: Electronic books